Clinical Profile and Bacteriological Patterns of Urinary Tract Infections in Hospitalized Pediatric Patients at Ngoerah Hospital - Ni Putu Ayu Elistya Ning Purwani; Gusti Ayu Putu Nilawati; I Made Karma Setiyawan (CV. Publikasi Indonesia, 2026)
Urinary tract infection (UTI) is a common bacterial infection in children, particularly among infants, and may lead to complications such as renal scarring and hypertension. Clinical manifestations vary according to age, with infants often presenting with nonspecific symptoms, while Escherichia coli is the most frequently identified pathogen, followed by other Gram-negative organisms. However, local data regarding bacterial patterns and clinical manifestations of pediatric UTIs at Ngoerah Hospital remain limited. This descriptive study aimed to characterize bacterial patterns and clinical features among children with UTIs who were hospitalized at Ngoerah Hospital from 2020 to 2025 using medical record data to strengthen local epidemiological evidence. A minimum of 100 patients was selected through consecutive sampling based on sample size calculations for descriptive categorical studies. Data were extracted from medical records, analyzed using SPSS version 20, and presented as frequency and percentage distributions. Among the 100 children with UTIs hospitalized at Ngoerah Hospital between 2020 and 2025, the highest proportion of cases occurred in the >5-year age group (51%), with a relatively balanced sex distribution. The most common clinical manifestation was fever (73%), followed by dysuria (18%). The bacterial etiology was predominantly composed of Gram-negative organisms, with Escherichia coli (38%) and Klebsiella pneumoniae (21%) identified as the most common pathogens, followed by Pseudomonas aeruginosa (12%), Proteus mirabilis (7%), and Enterococcus faecalis (4%). Overall, pediatric UTIs at Ngoerah Hospital between 2020 and 2025 were most frequently observed among children aged >5 years and commonly presented with fever, with Escherichia coli identified as the predominant causative organism.